2010
DOI: 10.1186/1472-6963-10-187
|View full text |Cite
|
Sign up to set email alerts
|

A pre-post test evaluation of the impact of the PELICAN MDT-TME Development Programme on the working lives of colorectal cancer team members

Abstract: BackgroundThe PELICAN Multidisciplinary Team Total Mesorectal Excision (MDT-TME) Development Programme aimed to improve clinical outcomes for rectal cancer by educating colorectal cancer teams in precision surgery and related aspects of multidisciplinary care. The Programme reached almost all colorectal cancer teams across England. We took the opportunity to assess the impact of participating in this novel team-based Development Programme on the working lives of colorectal cancer team members.MethodsThe impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…25,26 In addition, the satisfaction of patients and healthcare professionals are increasingly seen as important measures of the effectiveness of healthcare. 27,28 The results of this study should be interpreted in the light of certain limitations. First, the sample of MDT meetings comes from a single hospital and may not be representative of MDTs in general.…”
Section: Discussionmentioning
confidence: 91%
“…25,26 In addition, the satisfaction of patients and healthcare professionals are increasingly seen as important measures of the effectiveness of healthcare. 27,28 The results of this study should be interpreted in the light of certain limitations. First, the sample of MDT meetings comes from a single hospital and may not be representative of MDTs in general.…”
Section: Discussionmentioning
confidence: 91%
“…Education programmes directed primarily at surgeons have been shown to improve the oncological quality of surgical specimens and patient outcomes in Netherlands, Norway and Sweden [13] . The National Pelican MDT TME Development Programme was an educational programme aimed at the whole CRC MDT and was delivered through the Pelican Cancer Foundation in England [36] . Although there is limited evidence for the direct effect of the programme, outcomes for rectal cancer patients in the UK were significantly improved over this time period and a further government funded National MDT educational programme focusing on low rectal cancer called the Low Rectal Cancer Development Programme (LOREC) was launched a few years later [37] .…”
Section: The Role Of Mdt Education In Improving the Quality Of Treatmmentioning
confidence: 99%
“…In addition to the opportunity for education and self-appraisal and support for decision making, it has also been suggested that the cancer MDT meeting is enjoyed by some clinicians and that their job satisfaction improved as a result [46,47]. One of the predominant reasons for this seems to be the feeling that they provide their patients with a better service [47], and the MDT provides a means of monitoring and assessing services at both local and national levels.…”
Section: Benefits For the Patientmentioning
confidence: 99%
“…One of the predominant reasons for this seems to be the feeling that they provide their patients with a better service [47], and the MDT provides a means of monitoring and assessing services at both local and national levels. Important issues surrounding the care of an individual patient may be identified by one member of the team, or audits of MDT practice may be performed, which can be presented to the whole team so that changes to the service can be made with the input and agreement of all team members.…”
Section: Benefits For the Patientmentioning
confidence: 99%